Meta-analysis of the effects of physical activity on ocular biometrics in children and adolescents - Pengfei Nie; Pengfei Nie; Tong Feng; Tong Feng (Frontiers in Public Health)
IntroductionPhysical activity is recognized as an effective strategy for preventing myopia and cardiovascular diseases in children and adolescents; however, its impact on ocular biological parameters in this population remains poorly understood. This study systematically evaluates the effects of physical activity on ocular parameters in children and adolescents, aiming to provide a theoretical foundation for myopia and cardiovascular disease prevention.MethodsThe study was registered on PROSPERO (CRD4202454649). A comprehensive search of electronic databases—Web of Science, Embase, Cochrane Library, and PubMed—was conducted from their inception through April 2025. Two reviewers independently performed literature screening, data extraction, and risk-of-bias assessments using predefined inclusion/exclusion criteria. Methodological quality was evaluated using the PEDro and NOS scales, and outcomes were analyzed via network meta-analysis in RevMan 5.3.ResultsFourteen studies [8 randomized controlled trials (RCTs), 3 cross-sectional studies, 2 non-randomized controlled trials (NRCTs), and 1 cohort study] involving 12,548 participants aged 6–26 years were included. Meta-analysis revealed that physical activity significantly improved KVA (MD = 0.23, 95% CI = 0.18–0.29, p < 0.001), enhanced UDVA (MD = 0.2, 95% CI = 0.08–0.32, p < 0.001), delayed axial length (AL) progression (MD = 0.2, 95% CI = 0.08–0.32, p < 0.001), suppressed spherical equivalent refraction (SER) progression (MD = 0.2, 95% CI = 0.08–0.32, p < 0.001), reduced central retinal venular equivalent (CRVE) (MD = −2.50, 95% CI = −4.86 to −0.13, p = 0.04), and narrowed central retinal arteriolar equivalent (CRAE) (MD = −2.50, 95% CI = −4.86 to −0.13, p = 0.04). Physical activity demonstrably enhances dynamic and uncorrected distance vision, attenuates SER progression, and positively influences retinal vascular parameters.ConclusionRegular physical activity effectively slows myopia development and progression in children and adolescents while contributing to the prevention of cardiovascular diseases.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024546449.